Oath of Lucy Walker Smith - Smith, Lucy Walker
Transcript of an oath taken by Smith as to the circumstances of her marriage to Joseph Smith and to the divinity of plural marriage.
Positive photocopy.
Married Mormon leader Joseph Smith in Nauvoo, Ill., in 1843.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Smith, Joseph, -- Jr., -- 1805-1844.; Mormons; Polygamy